Teaching Speaking to Young Learners Through Role Play - Iin Inawati (Bandar Lampung University (UBL), 2014)
Role play is a potential activity which gives change for the students to enhance their speaking performance in a meaningful context. This study tries to investigate how the role play is implemented in teaching speaking in kindergarten context. Further, it also attempts to find out the kinds of speaking performance produced by the students during the teaching learning process. An exploratory case study research design was used in this study while the participants of this study were 22 students whose ages range between 5 and 6 years old. The data were gleaned from classroom observations, observation rating scale, and students’ daily learning records. Analysis of the data shows that teaching speaking to young learners in this study is conducted by implementing the sequence of activities that generally can be divided into three main stages, i.e. the activities before, during and after role play. The first stage is carried out as preparation to conduct the role play in the second stage while the last stage is conducted as a reflection from the teacher and students about the language which has been learnt and also about the teaching learning process. The other result from data analysis shows that the students can produce three kinds of speaking performance during the teaching learning process, these include: naming objects, producing simple sentences, and getting involved in a dialog. By conducting role play, the students are able not only to memorize and mention the word regardless its context but also use the language in meaningful contexts.